2019
DOI: 10.21894/jopr.2019.0043
|View full text |Cite
|
Sign up to set email alerts
|

Soil Bacterial Biodiversity in Development of Secondary Loggedover Forest to Oil Palm Plantation in Mineral Soil of Belaga, Sarawak

Abstract: Conversion of forest to oil palm typically results in significant land changes within the soil, for example, extensive damage to the top soil, soil compaction and erosion. Such changes are often related to reductions within the biodiversity and abundance of the soil microbial communities. By using 16S rDNA and denaturing gradient gel electrophoresis, we investigated the microbial composition between oil palm plantations, at various stages of planting in mineral soil of Belaga, Sarawak in Malaysia, and forest e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…A study by Miguel et al (2010) suggested that this method possibly detected multiple banding patterns attributed to sequence heterogeneity between copies of 16S rDNA strains, and one band may not necessarily represent one species. Recent studies have reported that unculturable bacteria were the dominant group in the study sites, followed by Proteobacteria, Acidobacteria, Firmicutes and Actinobacteria (Ahamed Bakeri et al, 2019;Ayob and Kusai, 2021;Maidin et al, 2016). The abundance of Acidobacteria in oil palm planted on peat soil suggested that due to the acidic environments, these bacteria grow under oligotrophic conditions.…”
Section: Denaturing Gradient Gel Electrophoresis (Dgge)mentioning
confidence: 94%
See 2 more Smart Citations
“…A study by Miguel et al (2010) suggested that this method possibly detected multiple banding patterns attributed to sequence heterogeneity between copies of 16S rDNA strains, and one band may not necessarily represent one species. Recent studies have reported that unculturable bacteria were the dominant group in the study sites, followed by Proteobacteria, Acidobacteria, Firmicutes and Actinobacteria (Ahamed Bakeri et al, 2019;Ayob and Kusai, 2021;Maidin et al, 2016). The abundance of Acidobacteria in oil palm planted on peat soil suggested that due to the acidic environments, these bacteria grow under oligotrophic conditions.…”
Section: Denaturing Gradient Gel Electrophoresis (Dgge)mentioning
confidence: 94%
“…In addition to that, phylum Acidobacteria was only detected using culture-independent methods (Ayob and Kusai, 2021). The fertiliser application increased in certain bacterial communities such as Firmicutes, in a 1.5-year-old oil palm plantation and this application also increased soil pH and phosphate content (Ahamed Bakeri et al, 2019).…”
Section: Denaturing Gradient Gel Electrophoresis (Dgge)mentioning
confidence: 99%
See 1 more Smart Citation